Interactions Between Apo E and Amyloid Beta and their Relationship to Nutriproteomics and Neurodegeneration - IJ, Martins; V, Gupta; AC, Wilson; SJ, Fuller; RN, Martins (Current Proteomics, 2014)
Proteomics has advanced and identified various plasma proteins that may be implicated in lesions in brains from neurodegenerative individuals. Apolipoprotein E and amyloid beta are amongst the many candidate proteins identified in common neurodegenerative disorders with effects by diet and nutriproteomics on the interactions of apo E and amyloid beta. The purpose of this review paper is to specify the role of proteins and lipoproteins and their effects on hepatic amyloid beta clearance that are important to brain amyloidosis. In recent and historical research provided in various research papers the blood brain barrier (BBB) is abnormal in neurodegenerative disease and proteins and oxidized lipids leak across the BBB. The improved scientific understanding of apo E/amyloid beta interactions identifies modulations in protein structure and lipid:protein interactions induced by nutrients and has become important to peripheral amyloid beta metabolism. Hepatic acute phase proteins induced by diet, inflammation and oxidative stress are connected to the pathophysiology of neurotoxic diseases. Oxidative stress induced by high cholesterol diets can cause electrostatic alterations in amyloid oligomers accompanied with alterations in oxidized lipids and acute phase proteins. Recent progress in proteomics with relevance to Alzheimer’s disease has led to the identification of acute phase proteins and include pentraxins that regulate or reduce amyloid beta sizes that are related to membrane permeability and disruption. In this review research papers identify acute phase biomarkers that are involved in the alterations of amyloid beta oligomers in obesity and diabetes with increased BBB permeability and central nervous system disorders.
Keywords: biomarkers